The Zinc Transporter ZnT3 Interacts with AP-3 and It Is Preferentially Targeted to a Distinct Synaptic Vesicle Subpopulation - Salazar, Gloria (American Society for Cell Biology, 2004)
Synaptic vesicles (SV) are generated by two different mechanisms, one AP-2 dependent and one AP-3 dependent. It has been uncertain, however, whether these mechanisms generate SV that differ in molecular composition. We explored this hypothesis by analyzing the targeting of ZnT3 and synaptophysin both to PC12 synaptic-like microvesicles (SLMV) as well as SV isolated from wild-type and AP-3-deficient mocha brains. ZnT3 cytosolic tail interacted selectively with AP-3 in cell-free assays. Accordingly, pharmacological disruption of either AP-2- or AP-3-dependent SLMV biogenesis preferentially reduced synaptophysin or ZnT3 targeting, respectively; suggesting that these antigens were concentrated in different vesicles. As predicted, immuno-isolated SLMV revealed that ZnT3 and synaptophysin were enriched in different vesicle populations. Likewise, morphological and biochemical analyses in hippocampal neurons indicated that these two antigens were also present in distinct but overlapping domains. ZnT3 SV content was reduced in AP-3-deficient neurons, but synaptophysin was not altered in the AP-3 null background. Our evidence indicates that neuroendocrine cells assemble molecularly heterogeneous SV and suggests that this diversity could contribute to the functional variety of synapses.